Diversity of Odonata in the urban ecosystem of Habiganj, Bangladesh (Bangladesh Journal of Zoology, 2025)
Dragonflies and damselflies are collectively known as odonates under the insect order Odonata. This group of insects is sensitive to environmental changes; therefore, acts as an ecological indicator. Field-based investigation on their diversity, abundance, and status is crucial to assess the ecological condition of any given landscape. Therefore, this study was carried out in an urban area of Habiganj Sadar Upazila between March 2020 and February 2021. Opportunistic surveys across different habitat types of two selected sites were followed for data collection. From the study, a total of 42 species of Odonata under 29 genera, 7 families, and 2 suborders have been recorded. Suborder Anisoptera contained the highest number of species (n=25), and Libellulidae was the dominant family (n=21) among 7 families. From the recorded species, 11 species were very common, 10 species were common, 6 species were uncommon, and 14 species were rare. Shannon-Wiener diversity index showed site A and the rainy season having the highest diversity (H′ = 3.1475 and H′ = 3.1119, respectively) of odonates. This preliminary study will provide information for future conservation steps for this charismatic insect group in the study area.Bangladesh J. Zool. 53(1): 19-30, 2025